Screening of potential microorganisms for the production of novel cyclodextrin glycosyltransferase (CGTase)enzyme - Nazrul Anuar, Ali (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Ten soil samples were collected from the vicinity of restaurant's drain where the wastewater contain remaining starch food constituent was filtered and drained away, housing estate ditch and trash waste disposal area around Kubang Kerian. They were screened for potential CGTase enzyme producer by culturing in media containing cassava starch and nutrient agar. A total of 40 colonies have been successfully isolated in this study by detecting the production of clearance zone around them, and those colonies were selected as CGTase producing bacteria. The CGTase producing bacteria were identified as Bacillus species by microscopy observation. The bacteria was grown in production medium containing 1.5% (w/v) cassava starch, 0.4% (w/v) (NH4)2S04, O.lM phosphate buffer (pH 7.0), 0.002% (w/v) MgS04 and 0.002% (w/v) FeS04 for the production of CGTase enzyme. The supernatant obtained after centrifugation at 3000 g for 15 minutes was used as crude enzyme. The activity of CGTase production was evaluated qualitatively by observing the production of clearance zone around the colony and quantitatively by determining the dextrinizing activity based on the method described by Fuwa, (1954) and Matsuzawa et al., (1975) with slight modification.